Comparative effectiveness of immediate-release and extended-release metformin on gastrointestinal tolerability, quality of life, and treatment satisfaction: a prospective cohort study - Alshadfan, Hisham; Mirghani, Hyder; Alrasheed, Tariq; Alanazi, Mansuor; Alatawi, Amirah; Elodemi, Mahmoud; Abdullah, Muhammad Nazrul Hakim (Wolters Kluwer Health, 2026)
Gastrointestinal (GI) side effects from metformin often limit its use and can impact patient quality of life (QoL) and satisfaction. The extended-release (XR) formulation is thought to cause fewer GI adverse events than immediate-release (IR) metformin, potentially improving tolerability, treatment satisfaction, and adherence. To compare metformin IR vs XR in terms of GI tolerability (incidence of GI side effects), patient-reported QoL, and medication satisfaction over 6 months in Saudi patients with type 2 diabetes. In a prospective cohort of 119 newly diagnosed patients with type 2 diabetes (62 on IR, 57 on XR), we tracked GI adverse events using a standardized questionnaire at baseline and 6-month follow-up. Diabetes-specific QoL was measured with the diabetes therapy-related quality of life questionnaire (DTR-QOL), and treatment satisfaction was assessed with the oral hypoglycemic agent questionnaire version 2 (OHA-Q ver. 2). Metformin XR was associated with significantly better GI tolerability. By 6 months, 45.2% of IR patients and only 24.5% of XR patients reported any GI side effect (P <.05). Rates of bothersome symptoms, such as diarrhea, were notably higher in the IR group. Patients on XR reported fewer interruptions of therapy due to GI upset. The DTR-QOL global score improved in both groups (P <.05), but there was no significant difference in total DTR-QOL scores between groups (P = .390). The OHA-Q ver. 2 global score improved in both groups (P <.05), but the XR group had higher scores in domains related to satisfaction (median treatment satisfaction domain score 100 vs 77.78 for IR, P < .05), with a significant difference in OHA-Q ver. 2 global score (92.59 vs 86.31 for IR; P <.05). Metformin XR demonstrated superior GI tolerability, which translated into improved treatment satisfaction compared to IR. While the overall quality of life related to diabetes management improved similarly with both, the XR formulation reduced side effect burden, and the lower daily dosing led to higher patient-reported satisfaction. These findings support the use of metformin XR to enhance tolerability and adherence, potentially leading to improved long-term outcomes.